Incumbents' asymmetric responses to environmentally friendly entrants in the automotive industry - Josefine Diekhof; Uwe Cantner (Friedrich Schiller University Jena, 2017)
In the context of technological change, the influence of innovative entrants on incumbents is considered a major driving force. Using global patent data, we analyze this influence for the case of the transition from combustion engine vehicles towards alternative technology vehicles (ATVs). Entrants play a key role in developing ATV-related patents, whereas automotive incumbents are considered as being less motivated in pursuing this new technology. Our results indicate that entrants' ATV-related knowledge accumulation stimulates incumbents' ATV-related research. Domestic entrants had a positive effect on the large incumbent majority that exhibited low ATV patent stocks whereas incumbents with high ATV patent stocks reacted with decreasing patenting; which is assumed to be a sign of R&D outsourcing or strategic acquisitions. Entrants in foreign countries yielded increasing incumbent responses along increasing incumbents' ATV patent stocks; which is in line with previously found competitive reactions to entry. Further, younger entrants, pre-entry patent- inexperienced entrants, and entrant leaders with greater technological relevance were more influential than their counterparts (old, experienced, and less technological relevant). This suggests that not only diversifying but also new establishments have an effect on incumbents. As technological leading and inexperienced entrants showed a stronger effect on incumbents but were outnumbered by their counterparts, it underpins that entrants with important characteristics and not the pure number of entrants drive these effects on incumbents.
Keywords: Q55; O3; Q52; R49; L91; L26; O31; 330; electric vehicle; entrepreneurship; environmental economics; industry dynamics; technological change; transport industry